Inverse Functions g(x) g ( x) if (f ∘g)(x) = x AND (g ∘f)(x) = x ( f ∘ g) ( x) = x AND ( g ∘ f) ( x) = x then we say that f (x) f ( x) and g(x) g ( x) are inverses of each other. More specifically we will say that g(x) g ( x) is the inverse of f (x)

PLEASE HURRY write the equation of the inverse function y=1/2cos^-1 (pix)-3 2 See answers Advertisement ujalakhan18 Answer: Step-by-step explanation: Firstly, we've to

To find the inverse of a function, you can use the following steps: 1. In the original equation, replace f (x) with y: to 2. Replace every x in the original equation with a y and every y in the original equation with an x Note: It is much easier to find the